Relevance of pre-analytical blood management on the emerging cardiovascular protein biomarkers TWEAK and HMGB1 and on miRNA serum and plasma profiling - Basso, Daniela; Weis, Tanja; Katus, Hugo (Clinical biochemistry, 2017)
Background: Disease-independent sources of biomarker variability include pre-analytical, analytical and biological variance. The aim of the present study was to evaluate whether the pre-analytical phase has any impact on the emerging heart disease TWEAK and HMGB1 protein markers and miRNA biomarkers, and whether peptidome profiling allows the identification of pre-analytical quality markers. Methods: An assessment was made of sample type (serum, EDTA-Plasma, Citrate-Plasma, ACD-plasma, Heparin-plasma), temperature of sample storage (room temperature or refrigerated), time of sample storage (0.5, 3, 6 and 9h) and centrifugation (one or two-step). Aliquots of all processed samples were immediately frozen (−80°C) before analysis. Proteins were assayed by ELISAs, miRNA expression profile by microarray and peptidome profiling by MALDI-TOF/MS. Results: Temperature, time and centrifugation had no impact on TWEAK and HMGB1 results, which were significantly influenced by matrix type, TWEAK levels being significantly higher (F=194.7, p<0.0001), and HMGB1 levels significantly lower (F=36.32, p<0.0001) in serum than in any other plasma type. Unsuitable miRNA results were obtained using Heparin-plasma. Serum miRNA expression profiles depended mainly on temperature, while EDTA-plasma miRNA expression profiles were strongly affected by the centrifugation method used. MALDI-TOF/MS allowed the identification of seven features as indices of pre-analytical serum (m/z at 1206, 1350, 1865 and 2021) or EDTA-plasma (m/z 1897, 2740 and 2917) degradation. Conclusions: Serum and EDTA-plasma allow the analysis of both proteins and miRNA emerging biomarkers of heart diseases. Refrigerated storage prevents an altered miRNA expression profile also in cases of a prolonged time-interval between blood drawing and processing.